Respiratory Syncytial Virus (RSV): Characteristics of Infection and the Role of Immune Response in the Evolution of Disease (Hematology Meeting Reports, 2009)
Infection with RSV is a major cause for hospitalizations of infants in the first year of life in the United States and most other parts of the world. Almost 100% of children are infected with this virus by 2-3 years of age. Normally, the infection is exquisitely restricted to the bronchopulmonary mucosa. However, development of extrapulmonary disease is observed in patients with certain T and B cell immunodeficiency states. The spectrum of illness associated with RSV is diverse and ranges from asymptomatic infection, mild upper airway disease, otitis media, apnea in the early neonatal period, or severe respiratory tract disease associated with bronchiolitis, pneumonia, wheezing or sudden infant death syndrome (SIDS). A small number of children will develop long term abnormalities of pulmonary function, episodes of wheezing or established reactive airway disease after severe disease or bronchiolitis. The immune response to primary infection is modest at best, but reinfection is followed by a robust booster effect with sustained antibody and cell mediated immune responses in both systemic and respiratory mucosal sites. The role of viral specific immune responses such as development of T-helper CD4+ Th1, Th2; IgE; viral induced cytokines; and suppressor cytotoxic CD8+ T cells, chemokines; leukotrienes and other cellular metabolites; and the importance of viral infectious load in the development and the severity of disease has been studied extensively. Many studies in animal models and a few human investigations have related the pathogenesis and long term outcome of RSV infection to abnormal or increased Th2 cytokine responses in a manner similar to other Th2-mediated allergic disorders. However, more recent investigations have also demonstrated that CD8+ T cell responses, non T cell derived pro-inflammatory cytokines and chemokine production, and the magnitude of viral load generated as a result of viral replication in the mucosa may be more important than Th2 responses in determining the outcome of acute infection and the development of long-term complications. It is still not clear if the association of RSV infection with long term wheezing is a reflection of primary immunologic hyperactivity, underlying genetic predisposition for atopic immune responses or direct effect of viral-induced cytolytic mucosal damage.